Menciptakan Ruang Siber yang Kondusif bagi Pegiat Anti-Korupsi - Wijayanto Wijayanto; Nur Hidayat Sardini; Gita N. Elsitra (Komisi Pemberantasan Korupsi, 2021)
This research aims to reflect cyber-terror cases in the anti-corruption movement by Indonesian scholars in protest against the revision of the KPK Law in September 2019 and formulates the alternative solutions for anti-corruption activists’ cyber safety in the digital era. Based on focus group discussion with anti-corruption scholar activists and digital ethnography, this research found that, in general, anti-corruption activist prone to cyber-terror, and it weakened their movement. For strengthening the anti-corruption movement in the digital era, this research formulated three alternative solutions, which are: 1) strengthening consolidation of civil society organizations; 2) supporting the formulation of comprehensive cyber regulations; and 3) implementing campus mitigation. Those solutions could be the foundation for fulfilling and guaranteeing anti-corruption activists’ digital rights, especially for the freedom of expression and right to be protected in cyber-space, which is crucial for digital democracy in Indonesia.